Petrology and Genesis of the Italian Zeolite Tuffs Used in the Construction Industry - Michael G. Stamatakis; Charalampos Vasilatos; Ioanna Stefania Stamataki (Materials Proceedings, 2021)
The Italian zeolitic tuffs have been intensely exploited by family companies and are used, mainly, as building, insulation and decorative stone, whereas the fine powder resulted during the cutting of the blocks is used for feedstock and soil amendment. XRD, XRF and SEM/EDS techniques have been applied to study the zeolitic samples collected from quarries of Naples, Bolsena and Sorano areas. Two different types of chabazite, have been identified; a Ca-rich and a Ca, Mg, K, Na-rich, both accompanying K- and Na-rich phillipsite probably due to the chemistry of the original volcanic glass, but also to the presence of alkali and alkaline earths-rich pore fluids. All tuffs studied exhibit shoshonitic affinity and trachytic composition. The occurrence of glassy tuffs above those zeolitized tuffs studied, is a characteristic model for an early zeolite diagenesis of the volcanic glass in open hydrological systems.